2023
DOI: 10.21037/tcr-22-2323
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of nomograms to predict early death in non-small cell lung cancer patients with brain metastasis: a retrospective study in the SEER database

Abstract: Background: Throughout the course of non-small cell lung cancer (NSCLC), a lot of patients would develop brain metastasis (BM) associated with the poor prognosis and high rate of mortality. However, there have been few models to predict early death (ED) from NSCLC patients with BM. We aimed to develop nomograms to predict ED in NSCLC patients with BM. Methods:The NSCLC patients with BM between 2010 and 2015 were selected from the Surveillance, Epidemiology, and End Result (SEER) database. Our inclusion criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…In our study, the patients who received chemotherapy had a much better prognosis than those without chemotherapy (7 vs. 2 months, P<0.001). Similarly, prior studies suggested that chemotherapy made a large contribution to the survival outcomes for NSCLC patients with brain or bone metastasis ( 24 , 25 , 36 - 38 ). Moreover, given that LM was significantly related to dismal prognosis in patients who had targeted therapy and immunotherapy ( 10 - 12 , 14 - 16 ), chemotherapy still plays an essential role in the setting of LM.…”
Section: Discussionmentioning
confidence: 77%
“…In our study, the patients who received chemotherapy had a much better prognosis than those without chemotherapy (7 vs. 2 months, P<0.001). Similarly, prior studies suggested that chemotherapy made a large contribution to the survival outcomes for NSCLC patients with brain or bone metastasis ( 24 , 25 , 36 - 38 ). Moreover, given that LM was significantly related to dismal prognosis in patients who had targeted therapy and immunotherapy ( 10 - 12 , 14 - 16 ), chemotherapy still plays an essential role in the setting of LM.…”
Section: Discussionmentioning
confidence: 77%